2015
DOI: 10.1513/annalsats.201501-061bc
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Pulmonary and Critical Care Training Program Directors toward Quality Improvement Education

Abstract: Rationale: Quality improvement (QI) is a required component of fellowship training in pulmonary, critical care, and sleep medicine. However, little is known about how training programs approach QI education.Objectives: We sought to understand the perceptions of pulmonary, critical care, and sleep medicine training program directors toward QI education. Methods:We developed and fielded an internet survey of pulmonary, critical care, and sleep medicine training program directors during 2013. Survey domains inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…A recent single-center study found that, even after QI science education, residency and fellowship program directors lacked the necessary knowledge and skills to develop curricula (28). A survey of pulmonary/critical care program directors indicated, although 84% felt that the QI education was important in fellowship training, only 26% had participated in a formal QI curriculum, and only 51% felt their graduating fellows were capable of independently performing QI (29). Barriers included lack of time, fellow interest, and qualified faculty.…”
Section: Faculty Qi Proficiencymentioning
confidence: 99%
“…A recent single-center study found that, even after QI science education, residency and fellowship program directors lacked the necessary knowledge and skills to develop curricula (28). A survey of pulmonary/critical care program directors indicated, although 84% felt that the QI education was important in fellowship training, only 26% had participated in a formal QI curriculum, and only 51% felt their graduating fellows were capable of independently performing QI (29). Barriers included lack of time, fellow interest, and qualified faculty.…”
Section: Faculty Qi Proficiencymentioning
confidence: 99%
“… 2 Previously identified implementation challenges of QIPS education within subspecialty fellowship training programs include lack of faculty expertise, time constraints, and competing priorities amongst trainees and their mentors. 3 , 4 Furthermore, as QIPS education occurs across the continuum of physician development, educational efforts must be coordinated to reinforce content and advance skills in order to optimize learner engagement and avoid unnecessary duplication of learning activities. To promote this continuum of professional advancement for fellow-level learners in QIPS, practice and development of QIPS skills through the framework of leadership and scholarship—two competencies emphasized in fellowship training programs—are needed.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this increased emphasis on QI across the spectrum of medical education, in 2015, Kahn and colleagues surveyed pulmonary and critical care medicine fellowship program directors on attitudes regarding graduate medical training in QI ( 10 ). Although program directors recognized the importance of QI and reported widespread involvement of fellows in QI-related activities, lack of fellow interest, lack of qualified faculty, and lack of time were significant barriers to QI education ( 10 ). Furthermore, additional unanswered questions remain regarding instituting QI curricula across multiple levels of medical education.…”
mentioning
confidence: 99%
“…The requirement for trainee QI education, project involvement, and scholarship presents an opportunity for innovative QI scholarship in medical education. Traditionally, formal QI education has taken the form of didactics, reading lists, faculty-led workshops, and Internet-based education tools ( Figure 1 ) ( 10 , 11 ). Although these forms of education may provide the delivery of foundational QI concepts such as those of root cause analysis and QI models such as Plan-Do-Study-Act (PDSA), traditional approaches are also passive and time consuming ( 12 ).…”
mentioning
confidence: 99%